Phenomenology Study: Experience Of Heart Fatigue Patients With Fatigue - Sofwan Sofwan (Lembaga Pengembangan Kinerja Dosen, 2022)
Heart failure is the inability or failure of the heart to pump blood throughout the body to meet the needs of tissue, oxygen and nutrition adequately which will have an impact on health, namely shortness of breath, activity intolerance and psychological disorders. This qualitative study was conducted to explore the experiences of heart failure patients with fatigue, with 3 female and 2 male participants. There are 4 themes obtained in this study, namely the changes that are felt since heart failure, the efforts made by patients to overcome heart failure with fatigue, the support system used by patients in an effort to overcome heart failure problems with fatigue, the patient's expectations for service. On average, participants in this study experienced physical changes such as breaths, intolrenation of activity and psychological changes. for this reason, the hospital and medical surgical nurses must be able to consider independent actions that can be done at home as well as support from the hospital and counseling, especially new patients.